Analisis Sistem Pengendalian Intern Atas pemberian Kredit Pada PT. Suzuki Finance Indonesia Cabang Pontianak - B51110104, Jihan Yahya (Jurnal KIAFE, 2014)
This study entitled "Analysis of Internal Control System Of Financial Management In Local Government Pontianak regency." Problems in the study were: 1) whether the system of internal control on financial management in local government Pontianak regency has been carried out effectively 2) What factors are causing the ineffectiveness of the system of internal control of financial management in the Government District Pontianak. Research conducted using descriptive method. Techniques of data collection in this research; interviews, observation, research library. The data analysis technique used in this study is an analysis too